Interpretation of the Parrot Image in the Codex Cumanicus - Akhmed A. Glashev (Publishing house "Sreda", 2024)
The article is devoted to the interpretation of the drawing in one of the most significant written monuments of the Kipchak and Oghuz languages - Codex Cumanicus - the image of a parrot, which is contained in the German part of the monument on sheet 58v, which has not yet been the subject of attention of researchers studying the monument. The only work devoted to this interesting image is the article by A. G. Yurchenko (2010), in which he connects it with the Egyptian Kipchaks. However, this interpretation does not seem objective. The problems in interpreting the contents of Codex Cumanicus are explained by the fact that its study has so far been carried out only by Turkologists, limiting themselves to purely linguistic issues. Therefore, an interdisciplinary method was used to interpret the image of the parrot on the monument, involving data from cultural studies, art history, religious studies, source studies, ethnology and archeology. The image of the parrot carries an important and profound meaning, connected not with the culture of the Kipchaks of Egypt, but with the Christian tradition, in particular with the content of the German part of the Codex Cumanicus, with the image of the Virgin Mary and the immaculate birth of Jesus Christ, to whom a significant part of the fragments of the Bible translated into the Polovtsian language is dedicated and which are often depicted on medieval engravings with a parrot. The parrot acts as a symbol of the immaculate image of Mary and Christ.